Primary imatinib resistance in chronic myeloid leukemia patients in a developing country: BCR-ABL kinase domain mutations or BCR-ABL independent mechanisms? - E Yap; N R Tumian; R Z Azma; N A Sharifah; S Salwati; N H Hamidah; M H Elias; C L Wong (College of Pathologist, 2024)
Non-Indexed Publication